Whole‐field macro‐ and micro‐deformation characteristic of unbound water‐loss in dentin hard tissue. Issue 9 (5th June 2018) - Chen, Zhenning; Nadeau, Bobby; Yu, Kevin; Shao, Xinxing; He, Xiaoyuan; Goh, M. Cynthia; Kishen, Anil
Abstract : High‐resolution deformation measurements in a functionally graded hard tissue such as human dentin are essential to understand the unbound water‐loss mediated changes and their role in its mechanical integrity. Yet a whole‐field, 3‐dimensional (3D) measurement and characterization of fully hydrated dentin in both macro‐ and micro‐scales remain to be a challenge. This study was conducted in 2 stages. In stage‐1, a stereo‐digital image correlation approach was utilized to determine the water‐loss and load‐induced 3D deformations of teeth in a sagittal section over consecutively acquired frames, from a fully hydrated state to nonhydrated conditions for a period up to 2 hours. The macroscale analysis revealed concentrated residual deformations at the dentin‐enamel‐junction and the apical regions of root in the direction perpendicular to the dentinal tubules. Significant difference in the localized deformation characteristics was observed between the inner and outer aspects of the root dentin. During quasi‐static loadings, further increase in the residual deformation was observed in the dentin. In stage‐2, dentin microstructural variations induced by dynamic water‐loss were assessed with environmental scanning electron microscopy and atomic force microscopy (AFM), showing that the dynamic water‐loss induced distention of dentinal tubules with concave tubular edges, and concurrent contraction of intertubular dentin with convex profile. The findings from the current macro‐ and micro‐scale analysis provided insight on the free‐water‐loss induced regional deformations and ultrastructural changes in human dentin. Abstract : The whole‐field, 3‐dimensional (3D) measurements of a fully hydrated dentin using stereo‐digital image correlation (stereo‐DIC) were examined to investigate the mechanical integrity and unbound water loss mediated changes of a functionally graded hard tissue. Concentrated residual deformations, significant difference in the localized deformation characteristics and microstructural variations were observed. Stereo‐DIC was demonstrated to be a promising model that allows for the study of 3D biomechanical responses of 3D fully/partially hydrated hard tissue (dentin).